2023
DOI: 10.3389/fimmu.2023.1146612
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-linolenic acid pretreatment alleviates NETs-induced alveolar macrophage pyroptosis by inhibiting pyrin inflammasome activation in a mouse model of sepsis-induced ALI/ARDS

Abstract: BackgroundNeutrophil extracellular traps (NETs) can cause acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) by inducing macrophage pyroptosis. The purpose of this study was to find out whether pretreatment of alpha-linolenic acid (ALA) could inhibit NETs-induced macrophage pyroptosis in sepsis-induced ALI/ARDS, as well as to identify which inflammasome is involved in this process.MethodsLPS was instilled into the trachea to establish sepsis-induced ALI/ARDS in a mouse model. ​Lung injury was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Besides, ALA is a plant-derived ω-3 fatty acid that possesses anti-inflammatory properties. Recent studies have demonstrated that pretreatment with ALA can ameliorate LPS-induced ALI by not only reducing the release of IL-1β cytokines from apoptosis cells but also inhibiting the activation of Pyrin inflammasome-driven macrophage sepsis [ 132 , 133 ], offering a potential therapeutic option for managing ALI/ARDS through enteral nutrition.…”
Section: The Impact Of Free Fatty Acids and Its Derivatives On Alimentioning
confidence: 99%
“…Besides, ALA is a plant-derived ω-3 fatty acid that possesses anti-inflammatory properties. Recent studies have demonstrated that pretreatment with ALA can ameliorate LPS-induced ALI by not only reducing the release of IL-1β cytokines from apoptosis cells but also inhibiting the activation of Pyrin inflammasome-driven macrophage sepsis [ 132 , 133 ], offering a potential therapeutic option for managing ALI/ARDS through enteral nutrition.…”
Section: The Impact Of Free Fatty Acids and Its Derivatives On Alimentioning
confidence: 99%
“…The development of ALI is highly intricate, involving multiple mechanisms such as inflammation activation, 6 cell apoptosis, 21 oxidative stress injury, 22 and coagulation dysfunction. 23 It is widely believed that at the core of its pathogenesis is an uncontrolled inflammatory response.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…The current treatment strategies for this mechanism are also a hot spot. It is found that inflammatory cytokines such as IL-1β and TNF-α can alleviate inflammatory reactions and tissue damage (42,65). Anti-cytokine drugs such as tocilizumab, adalimumab and celastrol have been used clinically to treat ALI (66)(67)(68).…”
Section: Inflammatory Response Mediated Injurymentioning
confidence: 99%
“…They play an essential role in enhancing alveolar fluid clearance and reducing pulmonary inflammatory response (40). Due to the protective effect of alveolar epithelial cells on the lung tissue barrier, the onset of ALI can manifest as apoptosis of alveolar epithelial cells and damage to the alveolar wall capillary barrier (41,42). The mechanisms by which sepsis leads to the development of ALI are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%